SISTEM BASIS DATA PEMANTAUAN PARAMETER AIR BERBASIS INTERNET OF THINGS (IoT) DENGAN PLATFORM THINGSPEAK - Benedika Ferdian Hutabarat; Mardian Peslinof; M. Ficky Afrianto; Yoza Fendriani (JOURNAL ONLINE OF PHYSICS, 2023)
] This research aims to develop an Internet of Things (IoT)-based water parameter monitoring database system using the Thingspeak platform. This system is designed to monitor real-time water parameters such as temperature, water pH, and water turbidity. Sensors for monitoring these water parameters are installed on a Raspberry Pi microprocessor connected to the internet network. The data generated by the sensors and processed by the Raspberry Pi are then sent to the Thingspeak server. The database system developed in this research utilizes the features provided by the Thingspeak platform, such as data processing, visualization, and integration with other software. The data stored in the database can be accessed online through the dashboard provided by Thingspeak. The test results show that the IoT-based water parameter monitoring database system with the Thingspeak platform can function properly and provide accurate information on the monitored water conditions. The sensors installed on the water successfully sent data periodically to the Thingspeak platform every 10 seconds. The test results showed a deviation value of 0.9996 for the accuracy of the temperature parameter, where the accuracy value of the temperature varied from 96.30% to 100%. The average accuracy of the temperature measurement was 98.74%, and the average system error was 1.26%. The system accuracy test results range from 0.95 to 0.99. The testing was conducted on a laboratory scale, and in the future, this system can be developed for real-time water parameter monitoring over a longer period of time